Faunal survey and identification key for the trematodes (Platyhelminthes: Digenea) infecting Potamopyrgus antipodarum (Gastropoda: Hydrobiidae) as first intermediate host - Hechinger, Ryan F. (Zootaxa, 2012)
A diverse guild of digenean trematodes infects the New Zealand mud snail, Potamopyrgus antipodarum, as firstintermediate host. This manuscript offers an initial systematic treatment of these trematodes and relies on published andnew information. I list 20 trematode species, for which I provide taxonomic affinities, life-cycle information, and anidentification key. A species account section presents photographs, diagnostic information, additional descriptive notes,and information on relevant research concerning the listed species. The major aim of this manuscript is to facilitateresearch on this trematode guild by providing information and identification tools, and by highlighting gaps in our knowledge.